Jawabanmu

2014-09-10T21:04:02+07:00
( 3a + 2b )
( 3a + 2b )
---------------- x
2b dikali 2b = 4b^2
2b dikali 3a = 6ab
3a dikali 2b = 6ab
3a dikali 3a = 9a^2
maka hasilnya adalah = 4b^2 + 6ab+6ab+9a^2\\
=4b^2 + 12ab + 9a^2

4b^2+12ab+9a^2
3a + 2b
---------------------------------------- X
2b dikali 9a^2 = 18a^2b
2b dikali 12ab = 24a[tex]= 18a^2b + 24ab^2+8b^3+27a^3+36a^2b+12ab^2 \\ 
= 27a^3 + ( 18a^2b + 36a^2b ) + ( 24ab^2 + 12ab^2 ) + 8b^3\\
= 27a^3 + 54a^2b + 36ab^2 + 8b^3b^2[/tex]
2b dikali 4b^2 = 8b^3

3a dikali 9a^2 = 27a^3
3a dikali 12ab =36a^2b
3a dikali 4b^2 =12ab^2
maka hasilnya adalah
2014-09-10T21:14:36+07:00
(3a+2b)³
=((3a+2b)(3a+2b))(3a+2b)
=(3a(3a+2b)+2b(3a+2b))(3a+2b)
=(9a²+6ab+6ab+4b²)(3a+2b)
=(9a²+12ab+4b²)(3a+2b)
=9a²(3a+2b)+12ab(3a+2b)+4b²(3a+2b)
=27a³+18a²b+36a²b+24ab²+12b²a+8b³
=27a³+54a²b+24ab²+12b²+8b³